Injury to swimmers: bad luck, bad athletes or bad management - Blanch, P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Due to the high repetitious workload of swimming training, overuse injuries especially of the shoulder are a costly problem for swimming. Due to different logistical reasons long term injury surveillance in swimming has not been achieved and research is often around perceived risk factors examined retrospectively and/or cross-sectionally. The identified risk factors often place 'the blame' for injury on some sort of athlete inadequacy {genetic, flexibility, strength, technique). However the most consistent findings that occur in the literature related to injury are to do with training volume and structure. Training ramped up too quickly, taken too high or maintained at monotonous levels are all related to injury. This of course places considerable responsibility on the coach. The basic recording of injury history and injury costs associated with measurement of the load athletes are placed under is fundamental information required for swimming to advance in the area of injury prevention.